Megacities 2050 : environmental consequences of urbanization : proceedings of the VI International Conference on Landscape Architecture to Support City Sustainable Development /: environmental consequences of urbanization : proceedings of the VI International Conference on Landscape Architecture to Support City Sustainable Development. ([2017]) - Unknown
No abstract available